Common Financial Market of the EAEU: Concept, Structure and Problems of Formation - S. А. Agamagomedova (Евразийская интеграция: экономика, право, политика, 2024)
Aim. The purpose of the study is to substantiate the concept and structure of the common financial market of the Eurasian Economic Union, highlight the problems of its formation and ways to solve them. Tasks. The objectives of the study are: review and analysis of the definitions of the common financial market in the legal framework of the Eurasian Economic Union; highlighting key aspects of the development of the common financial market; defining its structure, problems of formation, proposing ways to solve them.Methods. Methods were used: institutional analysis, comparative analysis, system analysis to substantiate aspects of the formation and structure of the common financial market of the Eurasian Economic Union. The method of formal logical analysis was also used to clarify the concepts of the common financial market in various acts of the integration level.Results. Firstly, at the level of the Eurasian Economic Union, the concept and criteria of a common financial market have been established.Secondly, a broad and narrow understanding of the structure of the common financial market in the context of Eurasian integration is highlighted.Thirdly, the key aspects of the development of the common financial market are: expanding the range and accessibility of financial services; ensuring the rights of consumers of financial services and investors; security and transparency of financial services.Fourthly, the problems of forming a common financial market are highlighted, including the different levels of development of the markets of the integration member states, the weak sector of the securities and investment markets.Conclusions. The common financial market is part of Eurasian integration, the processes of formation of such a market are components of integration processes. The structure of the general financial market in the narrow sense includes the banking and insurance services sector, the securities market sector, and the relations between these sectors. A broad understanding of the structure of the general financial market additionally includes the tax, budget and currency areas.